2012
DOI: 10.1080/00914037.2011.617339
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antimicrobial Properties of p-Chloroacetophenone Oxime-Based Furan Resins

Abstract: A copolymer resin, p-chloroacetophenone oxime-furfuraldehyde (CAOFU), and a terpolymer resin, p-chloroacetophenone oxime-formaldehyde-benzoic acid (CAOFUBA), were synthesized in the presence of hydrochloric acid as catalyst. The structures of copolymer and terpolymer were established by FT-IR and 1 H NMR techniques. Molecular weight and polydispersity index were determined by gel permeation chromatography. The thermal stability was evaluated by thermogravimetric analyses (TGA). Softening temperatures (T s ) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The obtained residue was dissolved in diethylether, washed with a 5% NaOH solution twice and then washed by distilled water. Organic layers were collected and then dried over anhydrous MgSO 4 …”
Section: Synthesis Of Chma Monomermentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained residue was dissolved in diethylether, washed with a 5% NaOH solution twice and then washed by distilled water. Organic layers were collected and then dried over anhydrous MgSO 4 …”
Section: Synthesis Of Chma Monomermentioning
confidence: 99%
“…Functional groups give special characteristics to the polymers and can provide an approach to the subsequent modification of the polymers for specific applications. [1][2][3][4][5][6] Recently Degirmenci et al, synthesized mid-and end-chain cyclohexene functionalized polystyrene and poly(ε-caprolactone) and by epoxidation of the cyclohexene group. They obtained macromonomers with cyclohexene oxide functionality with potential for applications in photoinitiated cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the development of polymeric nanocomposites with high mechanical property and thermal stability has become a hot issue in related elds. [11][12][13][14][15][16][17][18] Polyhydroxyalkanoate (PHA) has prospective potential for biological engineering and protective packaging to replace conventional plastics due to its advanced properties such as complete biodegradability, good biocompatibility, environmental protection, and plastic thermal process ability. [19][20][21][22] Nevertheless, it is not fully competitive compared to conventional plastics because there are some drawbacks to limiting its further application.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of the VOFHA and previously reported CAOFU and CAOFUBA with respect to standard drugs. [22] Ciprofloxacin and amphotericin-B were used as standards for antibacterial and antifungal activity, respectively. The tested terpolymer VOFHA was dissolved in DMSO with concentration of 250 μg/mL.…”
Section: Antimicrobial Activity Of Terpolymermentioning
confidence: 99%